2013
DOI: 10.4028/www.scientific.net/msf.740-742.197
|View full text |Cite
|
Sign up to set email alerts
|

Step-Bunching Free and 30 μm-Thick SiC Epitaxial Layer Growth on 150 mm SiC Substrate

Abstract: The production of 150 mm-diameter SiC epi-wafers is the key to the spread of SiC power devices. Besides, step-bunching free surface leads to high-performance devices. We have developed the production technology of the epitaxial growth with smooth surface morphology for 4º off Si-face 4H-SiC epitaxial layers on 150 mm diameter substrates. The various area observations of the surface by optical surface analyzer, confocal microscope and atomic force microscope revealed that there was no conventional step-bunching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In the last two years few researchers showed results on 150 mm 4 • off SiC 4H epitaxy: in 2011, an American research group showed the first results, 24 all in all the results were very promising, only withinwafer doping uniformity showed a high value. In 2012, a Japanese group showed free step bunching surface on their 150 mm SiC-4H epitaxy, 25 but again within-wafer doping uniformity showed high values.…”
Section: Preliminary Results On 150 MM Sic-4h Epitaxymentioning
confidence: 99%
“…In the last two years few researchers showed results on 150 mm 4 • off SiC 4H epitaxy: in 2011, an American research group showed the first results, 24 all in all the results were very promising, only withinwafer doping uniformity showed a high value. In 2012, a Japanese group showed free step bunching surface on their 150 mm SiC-4H epitaxy, 25 but again within-wafer doping uniformity showed high values.…”
Section: Preliminary Results On 150 MM Sic-4h Epitaxymentioning
confidence: 99%
“…An effective way to reduce SiC device cost is to increase SiC wafer size. Indeed, the development of 150 mm 4H-SiC materials, including the epitaxial growth, has gained a lot of attentions [2,3]. The larger size 150 mm SiC epi-wafer is particularly attractive because it benefits from the existing 150 mm silicon fabrication lines, making it possible to substantially reduce the capital investment for SiC device fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…15,16) Recently, the density of those surface defects and stepbunching has been gradually decreasing with an improvement of the epitaxial growth conditions. 17,18) As a consequence, large-area surface defects such as obtuse triangular defects 19,20) and trapezoid-shaped defects 21) are conspicuous and become one of the dominant surface defects.…”
Section: Introductionmentioning
confidence: 99%